Association of inflammatory biomarkers with new functional morbidity at hospital discharge in children who survive severe sepsis - Perry-Eaddy, Mallory A.; Faig, Walter; Curley, Martha A. Q.; Weiss, Scott L. (Frontiers in Pediatrics, 2025)
ObjectiveNew functional morbidity is common in critically ill children who survive sepsis; yet, the underlying biological mechanisms, particularly the impact of inflammation, remain unknown. We sought to test the hypothesis that increased levels of inflammatory biomarkers during the acute phase of pediatric sepsis are associated with new functional morbidity at hospital discharge.MethodsWe conducted a post hoc secondary analysis of the MitoPSe clinical study, including N = 119 critically ill children who survived sepsis. Data collected included demographic and clinical variables and 31 inflammatory biomarkers collected at three distinct timepoints (within days 1–2 of PICU admission, days 3–5, and days 8–14). The primary outcome was new functional morbidity, defined as at least a one-point increase in the pediatric overall performance category from baseline to hospital discharge.ResultsNew functional morbidity occurred in 38 children (32%) and was associated with increased plasma levels of interleukin (IL)-6, IL-18, sIL-2Ra, MCP1, IL-8 (CXCL8), sIL-1RII, IL-10, MIP1a, and IL-2r and decreased RANTES (CCL5) (p < .001) at all three timepoints. However, after adjusting for differences in chronic comorbid conditions, hospital length of stay, number of organ dysfunctions, and severity of illness, absolute biomarker levels, and trajectories were not significantly different between patients with or without new functional morbidity at hospital discharge.ConclusionsIn this sample of critically ill children treated for sepsis, increased inflammatory biomarker levels and the trajectory of change during the acute phase of pediatric sepsis were not independently associated with new functional morbidity at hospital discharge. Inflammatory biomarker levels likely reflect illness severity and other clinical variables associated with illness. However, these biomarkers may still be useful in identifying patients at risk of developing functional morbidity, despite the lack of causation within this study.